High Salt Intake Augments Blood Pressure Responses During Submaximal Aerobic Exercise. Issue 10 (18th May 2020) - Babcock, Matthew C.; Robinson, Austin T.; Migdal, Kamila U.; Watso, Joseph C.; Martens, Christopher R.; Edwards, David G.; Pescatello, Linda S.; Farquhar, William B.
Abstract : Background: High sodium (Na + ) intake is a widespread cardiovascular disease risk factor. High Na + intake impairs endothelial function and exaggerates sympathetic reflexes, which may augment exercising blood pressure (BP) responses. Therefore, this study examined the influence of high dietary Na + on BP responses during submaximal aerobic exercise. Methods and Results: Twenty adults (8F/12M, age=24±4 years; body mass index 23.0±0.6 kg·m −2 ; VO2 peak=39.7±9.8 mL·min −1 ·kg −1 ; systolic BP=111±10 mm Hg; diastolic BP=64±8 mm Hg) participated in this randomized, double‐blind, placebo‐controlled crossover study. Total Na + intake was manipulated via ingestion of capsules containing either a placebo (dextrose) or table salt (3900 mg Na + /day) for 10 days each, separated by ≥2 weeks. On day 10 of each intervention, endothelial function was assessed via flow‐mediated dilation followed by BP measurement at rest and during 50 minutes of cycling at 60% VO2peak . Throughout exercise, BP was assessed continuously via finger photoplethysmography and every 5 minutes via auscultation. Venous blood samples were collected at rest and during the final 10 minutes of exercise for assessment of norepinephrine. High Na + intake increased urinary Na + excretion (placebo=140±68 versus Na + =282±70 mmol·24H −1 ; P <0.001) and reduced flow‐mediated dilation (placebo=7.2±2.4 versus Na + =4.2±1.7%; P <0.001). Average exercising systolic BP was augmented following high Na + (placebo=Δ30.0±16.3 versus Na + =Δ38.3±16.2 mm Hg; P =0.03) and correlated to the reduction in flow‐mediated dilation ( R =−0.71, P =0.002). Resting norepinephrine concentration was not different between conditions ( P =0.82). Norepinephrine increased during exercise ( P =0.002), but there was no Na + effect ( P =0.26). Conclusions: High dietary Na + augments BP responses during submaximal aerobic exercise, which may be mediated, in part, by impaired endothelial function.